Improving Social Engagement and Initiations between Children with Autism Spectrum Disorder and Their Peers in Inclusive Settings - Koegel, Lynn Kern (2012)
Children with Asperger’s Disorder often have difficulty with peer relationships and socialization. The current study assessed whether peer social interactions would improve in school settings if an intervention was designed that incorporated the children with Asperger’s interests. Three children who were fully-included in regular education classes but did not interact with peers prior to intervention participated in this research. Social lunch clubs, open to both the study participants and their typical peers, were implemented twice weekly during regular lunchtime periods. Results showed that all three children increased their time engaged with peers as a result of the clubs. While their initiations greatly improved over baseline levels and approximated their peers, they were often initiating below the level of most of their peers. Implications for improving peer social interactions for children with Asperger’s Disorder are discussed.